Does Composition of Public Expenditure affect Economic growth? Evidence from Kenya - Maina, Rebecca Wanjiku; Nyandemo, Dr. S. M.; Kioko, Dr. Urbanus (International Journal of Economics, 2016)
Purpose: The main purpose of this study was to examine the impact of public expenditure on economic growth in Kenya with a view of establishing which specific components of government expenditure have significant impact on economic growth. Methodology: The analysis was presented in the framework of a simple neoclassical production function of Cobb-Douglas production equation. Econometric model was used to link between various components of government expenditure and economic growth without pre-judging which area should be productive or unproductive. The study examined the properties of time series, after which the regression was estimated using ordinary least squares method. Testing unit root tests, co integration test and granger causality tests was also carried. Error correction model was used to guard against the possibility of a spurious relationship while maintaining the level information. Results: Descriptive statistics indicates that there has been a steady increase in the real GDP from 1980 up until 2007 where a decrease was recorded. Jarque-Bera test statistic revealed that real agriculture, capital, defense, education, health, order and safety and transport expenditures are not normally distributed while GDP and labor were normally distributed. Bivariate correlation results presented indicate that there is a very strong and significantly positive correlation between the independent variables. This implies that the two variables could be multi correlated. The test results of the unit roots indicated that all variables are non-stationary. The model r squared was 0.998. This implied that the goodness of fit of the model was satisfactory as 99.8% of the variation in GDP was explained by the independent variables. The overall model was significant as demonstrated by an F statistic of 1480.4 (p value= 0.000). This further implied that the independent variables were good joint good predictors of long run GDP Unique contribution to theory, practice and policy: The study recommends that government should spend in key areas that are likely to stimulate growth. Resources should be channeled to the education as it has a significant effect on GDP. It is also recommended that political instability should be addressed since it has a negative effect on GDP.